Effect of Pulse Frequency on Tribological Behaviour of Functionally Graded Ni/Al2O3 Nanocomposite Coatings. (2015) - Siahpoosh, H.; Abbasi, A.R.; Aliofkhazraei, M.; Khajavi, B.; Majidi, H.
Abstract: The research on nanocomposite coating has been quite intensive in the past decade. The main goal of this research is study of effect of pulse frequency on properties of functionally graded Ni/Al2O3 nanocomposite coatings produced by ultrasound-assisted pulse electrodeposition. By changing the pulse frequency from 100 to 400 Hz during electrodeposition process, particle content in cross section of composite coating significantly was increased. The morphology of these coatings studied by scanning electron microscopy (SEM) that showed the content of nanoparticles in coatings was increased by decreasing duty cycle and frequency. Moreover, tribological behavior of these coating evaluated by the pin-on-disc type wear tester and Vickers micro-hardness instrument. The results showed changing the duty cycle 80 to 20% in the frequency 100 and 400 Hz, microhardness through coating increased while increasing frequency decreased microhardness of coating. By increasing frequency, the wear rate of coatings significantly increased.